Purification of simulated waste water using green synthesized silver nanoparticles of Piliostigma thonningii aqueous leave extract. (29th August 2017) - Shittu, K O; Ihebunna, O
Abstract: Synthesis of nanoparticles from various biological systems has been reported, but among all such systems, biosynthesis of nanoparticles from plants is considered the most suitable method. The use of plant material not only makes the process eco-friendly, but also the abundance makes it more economical. The aim of this study was to biologically synthesize silver nanoparticle using Piliostigma thonningii aqueous leaf extract and applied in the purification of laboratory stimulated waste with optimization using the different conditions of silver nanoparticle production such as time, temperature, pH, concentration of silver nitrate and volume of the aqueous extract. The biosynthesized silver nanoparticles were characterized by UV–visible spectrophotometry, nanosizer, energy dispersive x-ray analysis (EDX), transmission electron microscopy (TEM) and Fourier transform infrared (FTIR) spectroscopy. The time intervals for the reaction with aqueous silver nitrate solution shows an increase in the absorbance with time and became constant giving a maximum absorbance at 415 nm at 60 min of incubation. The pH of 6.5, temperature 65 °C, 1.25 mM of silver nitrate and 5 ml of plant extract was the best condition with maximum absorbance. The results from nanosizer, UV–vis and TEM suggested the biosynthesis silver nanoparticle to be spherical ranging from 50 nm to 114 nm. The EDX confirmed the elemental synthesis of silver at 2.60 keV and FTIR suggested the capping agent to be hydroxyl (OH) group with –C=C stretching vibrations. The synthesized silver nanoparticle also shows heavy metal removal activity in laboratory simulated waste water. The safety toxicity studies show no significant difference between the orally administered silver nanoparticles treated water group and control group, while the histopathological studies show well preserved hepatic architecture for the orally administered silver nanoparticle treated waste water group when compared with the control group. Therefore, it can be concluded that the biosynthesized silver nanoparticles have efficient ability in heavy metal removal without sub chronic adverse effects in experimental rats.